IMPLEMENTATION OF COST-EFFECTIVE SELF-HEALING APPROACH FOR RELIABLE HARDWARE SYSTEMS - Kumar, G. Harish; D, Mamatha.; Shivani, K.; Nikitha; Nandini, M. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The advance of sub-micron technology has resulted in the adversity of VLSI testing. Analysis and architecture for testability are accustomed today as analytical to an acknowledged design. Field Programmable Gate Arrays (FPGAs) accept been acclimated in abounding areas of agenda design. Because FPGAs are reprogrammable, faults can be calmly adequate already accountability sites are located. This cardboard presents a new able selfhealing arrangement that achieves 100% accountability advantage with low breadth overhead, and after any modification of the ambit beneath analysis (CUT) as 64- bit ALU, i.e., no analysis point insertion. Effective SelfHealing Approach for Reliable Hardware Systems. The proposed self-healing approach is applied to investigate for existing cell based and extension ALU array. Self-healing system components which observe not only potential problems but can also take steps to continue operation under Index Terms- Memory BIST, Address Generation, ALU-based implementation